EXPERIMENTAL VERIFICATION OF METHODS OF TEACHING FUTURE INTERNATIONAL ECONOMICS SPECIALISTS PROFESSIONALLY ORIENTED ENGLISH LISTENING COMPREHENSION IN SELF-STUDY WORK - Nadiya Hupka-Makohin (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The results of the experiment that prove the effectiveness of the suggested methods of teaching future international economics specialists professionally oriented English listening comprehension self-study work have been analysed. The methods are based on the principles of personal, reflective and professionally oriented approaches; presupposes simultaneous development of learning and strategic competence as the basis of learner autonomy; stage-by-stage professionally oriented English listening competence forming; providing students with more independence and encouraging their reflection. The estimation criteria of the future international economics specialists' professionally oriented English listening competence have been grounded (general comprehension of the text, detailed comprehension of the text, identifying specific information, the ability to analyse the information presented).